Reliability‐based design optimization of a car body using dimension‐ reduced Chebyshev polynomial. (22nd October 2022) - Li, Feng; Zhou, Yichen; Wei, Tonghui; Li, Hongfeng
Abstract: A reliability‐based design optimization (RBDO) method of a car body is presented on basis of dimension‐reduced Chebyshev polynomial method (DCM). To improve calculation efficiency and save computational time, complex models are often approximated by metamodels in reliability analysis. Traditional metamodels require a large number of sample points, which is time‐consuming. To improve the efficiency, DCM is proposed to approximate the performance function of the car body. First, the performance function is decomposed by the dimension‐reduction method into a sum of univariate functions, which are then fitted through Chebyshev polynomials. The reliability of the car body is predicted by the Taylor expansion method and the fourth‐moment method. Finally, the result of RBDO is obtained using an improved adaptive genetic algorithm. The proposed method saves on the calculation time with high precision. Besides, the improved adaptive genetic algorithm reduces the number of iterations in the car body optimization and improves the efficiency.